Exploring the role of peers in addressing the toxic drug crisis in emergency departments / Explorer le rôle des pairs dans la lutte contre la crise des drogues toxiques dans les services d’urgence - Tarnow, Janelle; Metwally, Rita; Sidhu, Aven; Black, Jade; Stoneson, Tracy; Van Osch, Mary; Benoit, Kassaundra; Wood, Kim (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Pappin Communications, 2025)
Introduction: Health systems across Canada are facing high numbers of patients who use drugs (PWUD), have a diagnosed substance use disorder, or are experiencing a toxic drug poisoning event, necessitating innovative approaches to care. With high instances of toxic drug poisoning events, emergency department staff are facing increasing burnout and moral distress (Van Hout & O’Reilly, 2020). A quality improvement pilot-project was conducted with the aim of incorporating individuals with lived experience using unregulated drugs (i.e., peers) into emergency department teams to improve patient outcomes and enhance staff supports, in response to the significant impact of the toxic drug crisis on health-care systems.Methods: The project used an overarching Plan-Do-Study-Act (PDSA) quality improvement framework, and a mixed-methods, utilization-focused evaluation to assess the impacts of embedding peers into the emergency department. A mixed methods design was used to collect data from intake forms, patient/staff experience surveys, and a semi-structured focus group of peer support staff.Results: The most common reasons for peer encounters (N = 764) were emotional support, harm reduction, referrals, witnessed consumption, and requests for basic necessities. The patient survey (N = 51) results demonstrated how the peers helped the majority of patients feel safe and more supported while accessing emergency care. ED staff (N = 22) shared positive experiences in the survey about the new peer program, highlighting improvements in patient support, increased access to harm reduction services, and the development of a more trusting healthcare system. During focus groups, peers (N = 2) outlined the importance of having this role embedded into emergency departments to ensure patients are receiving the care they need in a high-stress environment that, historically, has had the potential to cause significant harm through stigma and biases to PWUD.Conclusion: Integrating peers in the ED during the toxic drug crisis improved support for both patients and staff. This approach also has the potential to boost staff morale, reduce workload stress, decrease stigma toward PWUD, and enhance patient care. Overall, the hope is that integrating peers optimizes resources and strengthens both patient and provider experiences.